STRATEGI KOMUNIKASI PEMASARAN RUMAH BATIK ANDALAN PT RAPP DALAM MEMPROMOSIKAN BATIK BONO - Ririn Ratua Sari; Hevi Susanti; Sri Roserdevi Nasution (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Batik Bono is relatively new in the world of textile design in Indonesia. In 2013 a batik gallery was opened as a producer of bono batik with the brand "Batik Bono" in promoting or introducing products can be done through marketing communications. However, in reality bono batik does not just appear in the minds of consumers. Therefore, the company needs to know the marketing communication strategy that needs to be done so that the marketing is effective and the expected target can be achieved optimally. The purpose of this study is to find out how the Segmentation, Targeting, and Positioning of Rumah Batik Andalan in promoting Batik Bono and to find out how the Marketing Communication Strategy of Rumah Batik Andalan PT RAPP in Promoting Batik Bono relates to online advertising, sales promotion, personal selling and event marketing in promoting bono batik. This type of research is qualitative with the presentation of descriptive analysis. The research subjects are the Chairperson, Employees and Consumers with purposive techniques. Data collection techniques through observation, interviews and documentation. Data analysis using the Miler and Huberman models. Furthermore, for the Data Validity Check Technique using participation extension and triangulation. The results of this study indicate that the segmentation of Batik Bono is from the upper class such as government officials, companies, academics and organizations. Targeting, namely the government and academics, and Positioning, namely those who have unique patterns and motifs, and have isenan in every Bono batik cloth and use premium materials and the workmanship is handmade. The marketing communication strategy carried out is through online advertising (advertising online) using Instagram, Facebook and WhatsApp. Sales promotions are carried out in the form of price discounts and give aways and quizzes. Personal selling is done in the form of presentations to consumers regarding the product being promoted. Event marketing opens booths at certain events by teaching consumers education about the process of making batik. Keywords: Marketing Communication Strategy, Promotion, Batik Bono